Analisis Faktor Risiko Kejadian Hipertensi di Wilayah Kerja Puskesmas Letwaru Kota Masohi - Abidin, La Syam; Kainama, Norce (Jurnal Kesehatan Terpadu (Integrated Health Journal), 2024)
Background: Hypertension is still a cause of death worldwide. The prevalence of hypertension in Indonesia is still increasing. Literature review of hypertension risk factors tends to differ so new research is needed by combining all hypertension factors. Objectives: This study aims to analyze the determinant risk factors associated with the incidence of hypertension in the Letwaru Community Health Center work area. Methods: This study used a case-control design. The sample size was 148 respondents (74 cases and 74 controls). The sampling technique used cluster sampling. The research instrument used a questionnaire adopted and modified from several sources by adjusting the research objectives. Results: The results of logistic regression analysis showed; age (p value: 0.000, OR: 7.2), education level (p value: 0.001, OR: 0.53), family history of hypertension (p value: 0.005, OR: 4.1), and consumption of fatty/oily foods (p value: 0.037, OR: 0.35). Conclusion: Determinant risk factors related to the incidence of hypertension are age, education level, family history of hypertension, and consumption of fatty foods. Age is the most related determinant factor to the incidence of hypertension in the Letwaru Health Center work area. Recommendation: For the Letwaru Community Health Center to carry out routine blood pressure and cholesterol screening programs, health education on hypertension risk factors, hypertension diet education, and regular physical activity promotion targeting the elderly group